Assessment of heterotic patterns of tropical low-nitrogen–tolerant maize (Zea mays L.) inbred lines using testcross performance, morphological traits and SNP markers - Ajala, S.O.; Olayiwola, M.O.; Job, A.O.; Olaniyan, A.B.; Gedil, Melaku A (Wiley, 2020)
Breeding efforts in West and Central Africa (WCA) have focused on the development of Low‐N‐tolerant (LNT) maize inbreds and their classification into heterotic groups. This study was conducted to classify LNT maize lines into heterotic groups using testcross performance, morphological and SNP markers and to compare the consistency of groupings by the three methods. Thirty‐six LNT inbreds were crossed to two contrasting inbred testers to generate 72 testcrosses that were evaluated under low‐N conditions in Nigeria in 2014. Also, the 36 inbreds and the two testers were evaluated for per se performance under similar conditions as the testcrosses in 2014 and genotyped in 2015 using 1,123,196 SNP markers. Based on testcross performance, 33 of the 36 LNT inbreds were grouped by the two testers. Morphological characterization from per se performance and genetic relationship by SNP markers classified the inbreds into four groups that were inconsistent with their pedigree. Correlation analysis showed non‐concurrence of the three grouping methods. However, information from these groupings would assist in reducing the number of crosses to be made and evaluated.